Selective activation of anti-CD73 mechanisms in control of primary tumors and metastases. (4th May 2017) - Vijayan, Dipti; Barkauskas, Deborah S.; Stannard, Kimberley; Sult, Erin; Buonpane, Rebecca; Takeda, Kazuyoshi; Teng, Michele W. L.; Sachsenmeier, Kris; Hay, Carl; Smyth, Mark J.
ABSTRACT: The emerging role for CD73 in driving cancer growth and metastasis has presented opportunities to develop anti-CD73 monoclonal antibodies (mAbs) in the treatment of human cancers. Blockade of CD73 by antagonistic CD73 mAbs ameliorates tumor growth and metastasis via the inhibition of enzymatic and non-enzymatic CD73 pathways. In this study, we investigated whether Fc-receptor cross-linking represented a non-redundant mechanism by which anti-CD73 mAbs exert potent suppression of solid tumors and metastases. We engineered four anti-CD73 mAbs, each different in their ability to modulate CD73 enzymatic function and bind Fc receptors. mAbs recognizing a similar epitope of CD73 (CD73–04, TY/23 and 2C5) displayed the greatest antitumor activity. Importantly, we observed that the optimal control of metastasis by anti-CD73 mAbs involved primarily Fc receptor engagement, while suppression of solid tumors required both, enzyme inhibition and activation of Fc receptors. Engagement of Fc-receptors was also essential for optimal anti-metastatic effect in combination with either A2AR inhibitor or anti-PD-1 mAb treatment. The control of experimental metastases relied on the activation of host NK cells and IFNγ, while NK cells, CD8 + T cells and IFNγ were needed for effective antitumor effect in the spontaneous metastases model. These observations advance our understanding of the enzymatic and non-enzymatic functions of anti-CD73 mAbs in solid tumors and metastases. Altogether, these findings will greatly assist in the design of anti-CD73 mAbs to be used as either single agents or in combination with other immunotherapeutic molecules or targeted therapies.